1998
DOI: 10.1016/s0002-9440(10)65718-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of Human Immunoglobulin Heavy Chain Variable Genes (IgVH) in Normal and Malignant B Cells

Abstract: Antigen binding to the membrane-bound immunoglobulin (Ig) receptor is crucial for clonal survival during B cell development and antigenic stimulation of mature B cells. 41 Together with co-stimulatory signals (eg, CD40 and cytokines) it controls B cell proliferation and differentiation. 37 In the past, molecular analysis of Ig genes has been used mostly to prove clonality of a malignant lymphoproliferation. A detailed analysis, however, reveals that much more can be learned because clonal development, selectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 56 publications
0
43
1
Order By: Relevance
“…Immunoglobulin gene mutations accumulate during B-cell transit through the germinal center and are maintained after B-cell exit from the germinal center. 11,13 Recent evidence indicates that normal germinal center B cells also acquire mutations within the noncoding regions of the BCL-6 proto-oncogene. [14][15][16] Phenotypic B-cell markers include BCL-6 and CD10 proteins, which are expressed after germinal center entry, and MUM1 and CD138/syndecan-1 proteins, which are expressed during the late stages of B-cell maturation.…”
Section: Analysis Of Viral Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunoglobulin gene mutations accumulate during B-cell transit through the germinal center and are maintained after B-cell exit from the germinal center. 11,13 Recent evidence indicates that normal germinal center B cells also acquire mutations within the noncoding regions of the BCL-6 proto-oncogene. [14][15][16] Phenotypic B-cell markers include BCL-6 and CD10 proteins, which are expressed after germinal center entry, and MUM1 and CD138/syndecan-1 proteins, which are expressed during the late stages of B-cell maturation.…”
Section: Analysis Of Viral Infectionmentioning
confidence: 99%
“…Well-defined histogenetic markers of B-cell lymphoma currently include mutations of immunoglobulin and BCL-6 genes and expression of CD10, BCL-6, MUM1, and CD138/syndecan-1 antigens. [11][12][13][14][15][16][17][18][19] These markers are useful indicators of the origin and differentiation stage of B-cell lymphoma because each are retained upon neoplastic transformation.…”
mentioning
confidence: 99%
“…Ongoing mutation (intraclonal microheterogeneity) is linked to the germinal center (GC) microenvironment in normal immune reaction. 5 It is reported that FL has an intraclonal microheterogeneity resulting from the ongoing mutation which occurs in the neoplastic lesion, because FL tends to display a similar architecture to the normal reactive follicle. [26][27][28] However, it remains unclear whether B cell lymphomas with a diffuse architecture show intraclonal microheterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] The degree of somatic mutation found in VH genes from normal B cells depends on their level of differentiation during the immune response. Somatic mutation rates in various B cell neoplasms often correspond to those of their normal cellular counterparts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation